Wet-process injection material for bosh, bosh and lower part of furnace body of iron-making blast furnace and preparation method of wet-process injection material

By using plate-shaped corundum, titanium corundum and other materials in wet injection materials, and nitriding reaction to generate titanium nitride, the problem of insufficient wear resistance and service life of existing injection materials when used in the blast furnace belly, furnace waist and lower part of the furnace body is solved, and higher high-temperature performance and longer service life are achieved.

CN119591387APending Publication Date: 2025-03-11DALIAN KEMENG ENG MATERIALS CO LTD

Patent Information

Application Number
CN202411795768.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When used in the blast furnace belly, waist and lower part of the furnace body, the wear resistance, slag-resistant iron corrosion resistance and service life are insufficient, resulting in deformation of the blast furnace shape and increase the cost of iron smelting.

Method used

A wet injection material including plate-shaped corundum, titanium corundum, silicon carbide, alumina fine powder and silica fine powder is used, and spraying is carried out by stirring evenly and mixing with water. Titanium corundum nitride is used to generate titanium nitride to improve high temperature performance.

Benefits of technology

It significantly improves the high-temperature performance, wear resistance and slag-iron corrosion resistance of the injection material, extends the service life of the material, reduces the cost of iron smelting, and effectively utilizes the aluminum-titanium slag resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005176641460000071
    Figure BDA0005176641460000071
  • Figure BDA0005176641460000081
    Figure BDA0005176641460000081
Patent Text Reader

Abstract

The invention provides a wet-process injection material for a bosh, a bosh and the lower part of a furnace body of an iron-making blast furnace and a preparation method of the wet-process injection material. The injection material comprises the following components in parts by weight: 3-9 parts of tabular corundum particles of 3-6 mm, 23-33 parts of titanium corundum particles of 1-3 mm, 10-20 parts of titanium corundum particles of 0-1 mm, 0-6 parts of 88 high bauxite particles of 0-1 mm, 0-8 parts of 97 silicon carbide particles of 0-1 mm, 4-12 parts of 97 silicon carbide 45M powder, 6-13 parts of titanium corundum 200M powder, 4-8 parts of tabular corundum 325M powder and 4-7 parts of 71 pure calcium aluminate cement. The invention relates to a high-strength concrete, which is prepared from the following components in parts by weight: 5 to 10 parts of aluminum oxide micro powder, 5 to 10 parts of 96 silicon dioxide micro powder, 0.05 to 0.1 part of additive 1, 0.03 to 0.07 part of additive 2, 0.01 to 0.03 part of additive 3 and 0.05 to 0.1 part of additive 4. The wet-process injection material is used for being sprayed on the bosh, the bosh and the lower part of a furnace body of an iron-making blast furnace for lining making, so that the furnace shape can be quickly recovered, and various performance indexes such as high-temperature performance, wear resistance and slag iron corrosion resistance of the material can be improved, and the service life of the material on the parts can be greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of unshaped refractory materials, and in particular relates to a wet injection material for the bosh, waist and lower part of a furnace body of an iron-making blast furnace and a preparation method thereof. Background Art

[0002] Blast furnaces are smelting equipment that are in continuous high-temperature production for a long time. Due to the different working conditions of the linings of various parts of the blast furnace, the refractory materials and properties used for the lining of the blast furnace are also different. For example, the lining of the middle and upper parts of the furnace body mainly considers wear resistance, the lower part of the furnace body and the furnace waist mainly considers thermal shock damage and alkali metal erosion, and the belly mainly considers high FeO initial slag erosion. During the long-term service of the blast furnace belly, furnace waist and other parts, there are often multiple damage modes such as high-temperature molten iron erosion damage, thermal spalling damage and slag erosion. With the use of the blast furnace, the materials in this part are often eroded faster, which affects the furnace shape and leads to an increase in ironmaking costs and energy consumption. In order to solve the damage caused by the above extreme service conditions and effectively extend the life of the blast furnace, the research and development of injection materials is essential. At present, wet gunning lining technology has begun to be widely used in China. The technical feature is to use the blast furnace to stop the wind to gun the lining without stopping the furnace. Compared with the original traditional shutdown maintenance, wet gunning lining has the characteristics of convenient construction, less time consumption and fast production. The materials used in wet spraying technology are pre-mixed according to the designed water addition amount to form a mortar-like castable. This castable is mixed with atomized quick-setting agent at the nozzle of the spray gun and sprayed out. The castable instantly loses fluidity and adheres tightly to the surface to be sprayed. At present, the wet spraying technology adopts cement-bonded Al2O3-SiO2-SiC system spray coating, with a cement content of about 10%. Due to the large amount of cement, the material has poor strength in the medium and high temperature areas. At the same time, the liquid phase in the matrix is ​​relatively large when used at high temperature, resulting in the material's chemical corrosion resistance, airflow or material scouring resistance is relatively weak, and the toughness of the rigid bonded material is relatively poor, and the service life is relatively short, which affects the service life of the blast furnace. The longevity of the blast furnace is one of the signs of the development level of ironmaking technology. Extending the life of the blast furnace has always been a topic of concern for smelting engineering and technical personnel. Therefore, the selection and composition of the injection material using wet injection technology is very important. At present, the main material of the wet injection material is generally selected from brown corundum or bauxite raw materials, among which bauxite is a non-renewable mineral resource. Taking my country's existing bauxite reserves of 700 million tons as an example, according to the current mining rate, my country's bauxite resources will be mined out in less than 50 years. Brown corundum is made of bauxite and coke (anthracite) as the main raw materials and is smelted at high temperature in an electric arc furnace. It can be seen that when brown corundum is used as the main material of wet injection, it not only consumes non-renewable mineral resources, but also consumes high electricity and is expensive during processing. Compared with other means of blast furnace maintenance, it does not have a cost advantage and is not in line with the country's energy-saving industrial policy.

[0003] Aluminum-titanium slag is the slag waste produced in the process of smelting titanium-iron alloy. According to the alloy process, the titanium-iron alloy plant will produce slag equivalent to the amount of alloy every day. These wastes not only occupy land resources and aggravate the contradiction of shortage of arable land, but also cause huge pressure on enterprises and society in environmental governance. If these waste slags can be utilized, it can not only alleviate the environmental problems caused by the accumulation of a large amount of waste, but also provide a new way to prepare low-cost, high-performance refractory materials, which has important social significance and economic benefits. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a wet injection material for the bosh, waist and lower part of the furnace body of an iron-making blast furnace, which is used for spraying and lining the above parts to quickly restore the furnace shape, improve the material's high temperature performance, wear resistance, resistance to slag and iron corrosion and other properties, thereby greatly increasing the service life of the material in the above parts.

[0005] The present invention adopts the following technical solution:

[0006] A wet injection material for the bosh, waist and lower part of an ironmaking blast furnace, the injection material comprising the following components: 3-9 parts by weight of plate-shaped corundum 3-6 mm particles, 23-33 parts by weight of titanium corundum 1-3 mm particles, 10-20 parts by weight of titanium corundum 0-1 mm particles, 0-6 parts by weight of 88 high-alumina 0-1 mm particles, 0-8 parts by weight of 97 silicon carbide 0-1 mm particles, 4-12 parts by weight of 97 silicon carbide 45M powder parts by weight, 6-13 parts by weight of titanium corundum 200M powder, 4-8 parts by weight of plate-shaped corundum 325M powder, 4-7 parts by weight of 71 pure calcium aluminate cement, 5-10 parts by weight of alumina powder, 5-10 parts by weight of 96 parts by weight of silica powder, 1 0.05-0.1 parts by weight of admixture, 2 0.03-0.07 parts by weight of admixture, 3 0.01-0.03 parts by weight of admixture, and 4 0.05-0.1 parts by weight of admixture.

[0007] Furthermore, the injection material includes the following components: 5-7 parts by weight of plate-like corundum 3-6mm particles, 26-30 parts by weight of titanium corundum 1-3mm particles, 13-17 parts by weight of titanium corundum 0-1mm particles, 88 parts by weight of high-alumina 0-1mm particles, 2-4 parts by weight of 97 parts by weight of silicon carbide 0-1mm particles, 6-10 parts by weight of 97 silicon carbide 45M powder, 8-11 parts by weight of titanium corundum 200M powder, 5-7 parts by weight of plate-like corundum 325M powder, 71 parts by weight of pure calcium aluminate cement, 6-9 parts by weight of alumina powder, 96 parts by weight of silicon dioxide powder, 1 part by weight of additive, 0.06-0.09 parts by weight of additive, 2 parts by weight of additive, 0.015-0.025 parts by weight of additive, and 4 parts by weight of additive.

[0008] Furthermore, the injection material is composed of the following components: 6 parts by weight of plate-like corundum 3-6mm particles, 28 parts by weight of titanium corundum 1-3mm particles, 15 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 88 high-alumina 0-1mm particles, 4 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 45M powder, 9.5 parts by weight of titanium corundum 200M powder, 6 parts by weight of plate-like corundum 325M powder, 5.5 parts by weight of 71 pure calcium aluminate cement, 7.5 parts by weight of alumina powder, 7.5 parts by weight of 96 silicon dioxide powder, 0.075 parts by weight of 1 additive, 0.05 parts by weight of 2 additives, 0.02 parts by weight of 3 additives, and 0.07 parts by weight of 4 additives.

[0009] Furthermore, the Al2O3 content of the titanium corundum is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 .

[0010] Furthermore, the additive 1 is sodium hexametaphosphate.

[0011] Furthermore, the 2 admixtures are sodium tripolyphosphate.

[0012] Furthermore, the 3 admixture is 200M aluminum powder.

[0013] Furthermore, the 4 admixtures are explosion-proof fibers.

[0014] A method for preparing wet injection material for the bosh, waist and lower part of the furnace body of an iron-making blast furnace as described in any of the above items comprises the following steps: 1) adding all the raw materials in the formula into a high-powered mixer with a rotation speed of 20r / min in sequence and stirring for 5 minutes; 2) taking samples and measuring after the materials are completely stirred; 3) bagging and storing the materials after determining that the construction performance of the materials meets the requirements.

[0015] When the wet injection material for the bosh, waist and lower part of the furnace body of an iron-making blast furnace is used, the prepared injection material is added into a whole bag into a powerful mixer with a rotation speed of 20r / min and 5-6% by weight of water is added. After stirring for 5 minutes, the material is observed and pumped and sprayed after it is completely stirred.

[0016] The advantages and effects of the present invention are:

[0017] 1. Make full use of aluminum-titanium slag and add titanium furnace protection to the injection material. The principle that the low-priced titanium on the surface of the injection material will undergo nitridation reaction to form titanium nitride under the special environment of the blast furnace is utilized. Titanium nitride has a series of advantages such as high melting point, high hardness, wear resistance, resistance to slag iron erosion, resistance to slag iron infiltration, and high stability, thus giving the injection material better high-temperature performance.

[0018] 2. The spraying material construction method is convenient and easy to operate, and the spraying construction is carried out according to the normal spraying material construction method.

[0019] 3. The construction of this injection material is time-saving and efficient. It has the characteristics of injection material and can shorten the overall construction period.

[0020] 4. The injection material has excellent performance and is more suitable for the blast furnace bosh and furnace waist environment than general materials, which greatly extends the service life of the material, thereby ensuring the longevity of the blast furnace.

[0021] 5. Adding appropriate titanium to the injection material avoids a large amount of waste of titanium resources in the later stage of the blast furnace, thereby reducing ironmaking costs and energy consumption. DETAILED DESCRIPTION

[0022] The present invention will be further explained below in conjunction with the embodiments.

[0023] The invention provides a wet injection material for the furnace belly, furnace waist and lower part of the furnace body of an iron-making blast furnace and a preparation method thereof. The injection material comprises the following components: 3-9 parts by weight of plate-shaped corundum 3-6 mm particles, 23-33 parts by weight of titanium corundum 1-3 mm particles, 10-20 parts by weight of titanium corundum 0-1 mm particles, 0-6 parts by weight of 88 high-alumina 0-1 mm particles, 0-8 parts by weight of 97 silicon carbide 0-1 mm particles, 4-12 parts by weight of 97 silicon carbide 45M powder, 6-13 parts by weight of titanium corundum 200M powder, plate-shaped corundum, and the like. 325M powder 4-8 weight parts, 71 pure calcium aluminate cement 4-7 weight parts, alumina powder 5-10 weight parts, 96 silica powder 5-10 weight parts, 1 admixture 0.05-0.1 weight parts, 2 admixture 0.03-0.07 weight parts, 3 admixture 0.01-0.03 weight parts, 4 admixture 0.05-0.1 weight parts, wherein the Al2O3 content of the titanium corundum used is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the bulk density is ≥3.85g / cm 3 , the 1st additive is sodium hexametaphosphate, the 2nd additive is sodium tripolyphosphate, the 3rd additive is 200M aluminum powder, and the 4th additive is explosion-proof fiber.

[0024] The preparation method comprises: 1) adding all raw materials in the formula into a powerful mixer with a rotation speed of 20r / min in sequence and stirring for 5 minutes; 2) taking samples for measurement after the materials are completely stirred; 3) bagging and storing the materials after confirming that the construction performance of the materials meets the requirements.

[0025] When the injection material is used, the prepared injection material is put into a powerful mixer with a rotation speed of 20r / min, and 5-6% by weight of water is added. After stirring for 5 minutes, observe, and after the material is completely stirred, pump and spray construction is carried out.

[0026] Example 1

[0027] Take 3 parts by weight of plate-like corundum 3-6mm particles, 23 parts by weight of titanium corundum 1-3mm particles, 10 parts by weight of titanium corundum 0-1mm particles, 0 parts by weight of 88 high-alumina bauxite 0-1mm particles, 0 parts by weight of 97 silicon carbide 0-1mm particles, 4 parts by weight of 97 silicon carbide 45M powder, 6 parts by weight of titanium corundum 200M powder, 4 parts by weight of plate-like corundum 325M powder, 4 parts by weight of 71 pure calcium aluminate cement, 5 parts by weight of alumina powder, 5 parts by weight of 96 silicon dioxide powder, 0.05 parts by weight of sodium hexametaphosphate as an additive, 0.03 parts by weight of sodium tripolyphosphate as an additive, 0.01 parts by weight of 200M aluminum powder as an additive, and 0.05 parts by weight of explosion-proof fiber as an additive. The Al2O3 content of the titanium corundum used is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 The 1st additive is sodium hexametaphosphate, the 2nd additive is sodium tripolyphosphate, the 3rd additive is 200M aluminum powder, and the 4th additive is explosion-proof fiber. All the raw materials in the formula are added into a high-powered mixer with a rotation speed of 20r / min in sequence. After stirring for 5 minutes, the materials are completely stirred evenly. Samples are taken for measurement. After confirming that the construction performance of the materials meets the requirements, they are bagged and stored.

[0028] Example 2

[0029] Take 9 parts by weight of plate-like corundum 3-6mm particles, 33 parts by weight of titanium corundum 1-3mm particles, 20 parts by weight of titanium corundum 0-1mm particles, 6 parts by weight of 88 high-alumina 0-1mm particles, 8 parts by weight of 97 silicon carbide 0-1mm particles, 12 parts by weight of 97 silicon carbide 45M powder, 13 parts by weight of titanium corundum 200M powder, 8 parts by weight of plate-like corundum 325M powder, 7 parts by weight of 71 pure calcium aluminate cement, and 1 part by weight of alumina powder. 0 weight parts, 96 silicon dioxide powder 10 weight parts, 1 additive sodium hexametaphosphate 0.1 weight parts, 2 additive sodium tripolyphosphate 0.07 weight parts, 3 additive 200M aluminum powder 0.03 weight parts, 4 additive explosion-proof fiber 0.1 weight parts, wherein the Al2O3 content of the titanium corundum used is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes until the materials are completely mixed, take samples for measurement, and bag and store after confirming that the construction performance of the materials meets the requirements.

[0030] Example 3

[0031] Take 6 parts by weight of plate-like corundum 3-6mm particles, 28 parts by weight of titanium corundum 1-3mm particles, 15 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 88 high-alumina 0-1mm particles, 4 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 45M powder, 9.5 parts by weight of titanium corundum 200M powder, 6 parts by weight of plate-like corundum 325M powder, 5.5 parts by weight of 71 pure calcium aluminate cement, and 7 parts of alumina powder. 5 parts by weight, 96 parts by weight of silica powder, 7.5 parts by weight, 1 part by weight of sodium hexametaphosphate, 2 parts by weight of sodium tripolyphosphate, 3 parts by weight of 200M aluminum powder, 4 parts by weight of explosion-proof fiber, wherein the Al2O3 content of the titanium corundum used is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes until the materials are completely mixed, take samples for measurement, and bag and store after confirming that the construction performance of the materials meets the requirements.

[0032] Example 4

[0033] Take 5 parts by weight of plate-like corundum 3-6mm particles, 26 parts by weight of titanium corundum 1-3mm particles, 13 parts by weight of titanium corundum 0-1mm particles, 2 parts by weight of 88 high-alumina bauxite 0-1mm particles, 2 parts by weight of 97 silicon carbide 0-1mm particles, 6 parts by weight of 97 silicon carbide 45M powder, 8 parts by weight of titanium corundum 200M powder, 5 parts by weight of plate-like corundum 325M powder, 5 parts by weight of 71 pure calcium aluminate cement, 6 parts by weight of alumina powder, 6 parts by weight of 96 silicon dioxide powder, 0.06 parts by weight of sodium hexametaphosphate as an additive, 0.04 parts by weight of sodium tripolyphosphate as an additive, 0.015 parts by weight of 200M aluminum powder as an additive, and 0.06 parts by weight of explosion-proof fiber as an additive. The Al2O3 content of the titanium corundum used is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes until the materials are completely mixed, take samples for measurement, and bag and store after confirming that the construction performance of the materials meets the requirements.

[0034] Example 5

[0035] Take 7 parts by weight of plate-like corundum 3-6mm particles, 30 parts by weight of titanium corundum 1-3mm particles, 17 parts by weight of titanium corundum 0-1mm particles, 4 parts by weight of 88 high-alumina bauxite 0-1mm particles, 6 parts by weight of 97 silicon carbide 0-1mm particles, 10 parts by weight of 97 silicon carbide 45M powder, 11 parts by weight of titanium corundum 200M powder, 7 parts by weight of plate-like corundum 325M powder, 6 parts by weight of 71 pure calcium aluminate cement, and alumina powder. 9 parts by weight, 96 parts by weight of silicon dioxide powder, 1 part by weight of sodium hexametaphosphate as an additive, 2 parts by weight of sodium tripolyphosphate as an additive, 3 parts by weight of 200M aluminum powder as an additive, 4 parts by weight of explosion-proof fiber as an additive, wherein the Al2O3 content of titanium corundum is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes until the materials are completely mixed, take samples for measurement, and bag and store after confirming that the construction performance of the materials meets the requirements.

[0036] When using the spraying material prepared in Examples 1-5: add the whole package of the prepared spraying material into a powerful mixer with a rotation speed of 20r / min and add 5-6% by weight of water, stir for 5 minutes and observe, and after the spraying material is completely stirred and evenly mixed, pump and spray construction.

[0037] The following is a detailed description of this material from the perspective of the characteristics of a certain raw material contained in the formula:

[0038] (1) This material contains titanium corundum particles and fine powder. The specially purchased titanium corundum itself is composed of Al2O3 and Ti2O3, and Ti2O3 undergoes nitridation reaction to generate TiN in the internal environment of the blast furnace. Therefore, it has a series of advantages such as high melting point, high hardness, wear resistance, resistance to slag iron erosion, resistance to slag iron infiltration, and high stability, thus giving the injection material better high-temperature performance. ;

[0039] (2) This material contains plate-shaped corundum particles and fine powder. Due to its high purity and low melting point phase, it has high high temperature performance and stability, which further supports the service life of the material under extremely harsh conditions such as furnace bosh and furnace waist;

[0040] (3) Silicon carbide is added to this material to increase the thermal conductivity and wear resistance of the material. Since the blast furnace hearth is equipped with cooling walls as a whole, increasing the thermal conductivity of the material can effectively reduce the temperature of the hot end of the material, pushing the 1150°C isotherm into the furnace, and the stagnant slag iron layer formed can effectively protect the material from scouring and erosion;

[0041] (4) Alumina powder is added to the material. As a kind of powder, it has fine particle size and plays a filling role, reduces the amount of glue added to the material, increases the density of the material, and thus improves the performance of various materials;

[0042] (5) This material contains 96 silica powder, which is a kind of powder with fine particle size. It plays a filling role, reduces the amount of glue added to the material, increases the density of the material, and thus improves the performance of various materials.

[0043] Related experiments and data

[0044] 1. Experimental purpose:

[0045] The construction and use performances of a wet shotcrete used for the bosh, waist and lower part of the furnace body of an iron-making blast furnace and a common shotcrete were compared, and the data of the various properties of the two materials were analyzed to draw conclusions.

[0046] 2. Experimental steps:

[0047] (1) Material preparation: A wet shotcrete material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace (hereinafter referred to as "CM-TA 20G") and a common shotcrete material (hereinafter referred to as "CM-SHOTH10SC") were prepared according to the specified material preparation method.

[0048] (2) Sample preparation: In accordance with national standards, the material CM-TA 20G is prepared by casting using a 40mm×40mm×160mm mold; the material CM-SHOT H10SC is prepared by casting using a 40mm×40mm×160mm mold.

[0049] (3) Performance testing: According to the national standard, the working time and solidification time of CM-TA 20G and CM-SHOT H10SC were tested respectively, and the volume density, room temperature compressive strength, room temperature flexural strength and permanent linear change rate after firing at 110℃×24h, 815℃×3h and 1450℃×3h were tested respectively. The specific experimental data are shown in Table 1.

[0050] Table 1. Experimental data

[0051]

[0052]

[0053] (4) Data analysis and conclusion: As can be seen from Table 1, compared with "CM-SHOT H10SC", "CM-TA 20G" has better performance in terms of bulk density, room temperature pressure resistance, flexural strength and permanent linear change rate, and can fully meet the specific use requirements.

Claims

1. A wet injection material for the bosh, waist and lower part of the furnace body of an iron-making blast furnace, characterized in that: The injection material includes the following components: 3-9 parts by weight of plate-like corundum 3-6mm particles, 23-33 parts by weight of titanium corundum 1-3mm particles, 10-20 parts by weight of titanium corundum 0-1mm particles, 0-6 parts by weight of 88 high-alumina bauxite 0-1mm particles, 0-8 parts by weight of 97 silicon carbide 0-1mm particles, 4-12 parts by weight of 97 silicon carbide 45M powder, 6-13 parts by weight of titanium corundum 200M powder, 4-8 parts by weight of plate-like corundum 325M powder, 4-7 parts by weight of 71 pure calcium aluminate cement, 5-10 parts by weight of alumina powder, 5-10 parts by weight of silicon dioxide powder, 1 0.05-0.1 parts by weight of admixture, 2 0.03-0.07 parts by weight of admixture, 3 0.01-0.03 parts by weight of admixture, and 4 0.05-0.1 parts by weight of admixture.

2. The wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to claim 1, characterized in that: The injection material includes the following components: 5-7 parts by weight of plate-like corundum 3-6mm particles, 26-30 parts by weight of titanium corundum 1-3mm particles, 13-17 parts by weight of titanium corundum 0-1mm particles, 2-4 parts by weight of 88 high-alumina bauxite 0-1mm particles, 2-6 parts by weight of 97 silicon carbide 0-1mm particles, 6-10 parts by weight of 97 silicon carbide 45M powder, 8-11 parts by weight of titanium corundum 200M powder, 5-7 parts by weight of plate-like corundum 325M powder, 5-6 parts by weight of 71 pure calcium aluminate cement, 6-9 parts by weight of alumina micropowder, 6-9 parts by weight of 96 silicon dioxide micropowder, 0.06-0.09 parts by weight of 1 additive, 0.04-0.06 parts by weight of 2 additives, 0.015-0.025 parts by weight of 3 additives, and 0.06-0.08 parts by weight of 4 additives.

3. The wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to claim 2, characterized in that: The injection material is composed of the following components: 6 parts by weight of plate-like corundum 3-6mm particles, 28 parts by weight of titanium corundum 1-3mm particles, 15 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 88 high-alumina 0-1mm particles, 4 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 45M powder, 9.5 parts by weight of titanium corundum 200M powder, 6 parts by weight of plate-like corundum 325M powder, 5.5 parts by weight of 71 pure calcium aluminate cement, 7.5 parts by weight of alumina powder, 7.5 parts by weight of 96 silicon dioxide powder, 0.075 parts by weight of 1 additive, 0.05 parts by weight of 2 additives, 0.02 parts by weight of 3 additives, and 0.07 parts by weight of 4 additives.

4. A wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The titanium corundum has an Al2O3 content of 55-75%, a Ti2O3 content of 20-40%, an impurity content of ≤5%, and a bulk density of ≥3.85 g / cm 3 .

5. A wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The additive 1 is sodium hexametaphosphate.

6. A wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The 2 admixtures are sodium tripolyphosphate.

7. A wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The 3 admixture is 200M aluminum powder.

8. A wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The 4 admixtures are explosion-proof fibers.

9. A method for preparing wet injection material for the bosh, waist and lower part of the furnace body of an ironmaking blast furnace according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Add all the ingredients in the formula into a high-powered mixer at a speed of 20 r / min and stir for 5 minutes; 2) After the materials are completely mixed, take samples for measurement; 3) After confirming that the construction performance of the materials meets the requirements, bag them for storage.

10. The method for preparing wet injection material for the bosh, waist and lower part of the furnace body of an iron-making blast furnace according to claim 9, characterized in that: When using, add the whole package of prepared injection material into a powerful mixer with a rotation speed of 20r / min, add 5-6% by weight of water, stir for 5 minutes and observe, and after the material is completely stirred and evenly mixed, pump and spray for construction.

Citation Information

Patent Citations

  • High-strength castable

    CN101712560A

  • Self-healing type wet-process spray coating for repairing ladle and spray coating method of self-healing type wet-process spray coating

    CN118184305A

Cited By

  • Titanium calcium aluminate refractory material taking aluminum titanium slag as raw material and preparation method of titanium calcium aluminate refractory material

    CN121609559A